Mobile phone text messaging for promoting adherence to anti-tuberculosis treatment: a systematic review - Nglazi, Mweete D; Bekker, Linda-Gail; Wood, Robin; Hussey, Gregory D; Wiysonge, Charles S (BMC infectious diseases, 2013)
Mobile phone text messaging (SMS) has the potential to promote adherence to tuberculosis treatment. This systematic review aims to synthesize current evidence on the effectiveness of SMS interventions in improving patients' adherence to tuberculosis treatment. We searched electronic databases (PubMed, EMBASE, Science Citation Index), reference lists of relevant articles, conference proceedings, and selected websites for eligible studies available by 15 February 2013; regardless of language or publication status. Two authors independently screened selected eligible studies, and assessed risk of bias in included studies; resolving discrepancies by discussion and consensus. We identified four studies that compared the outcomes of the SMS intervention group with controls. Only one of the four studies was a randomized controlled trial. This was conducted in Argentina and the SMS intervention did not significantly improve adherence to tuberculosis treatment compared to self-administration of tuberculosis treatment (risk ratio [RR] 1.49, 95% confidence intervals [CI] 0.90 to 2.42). One of the non-randomized studies, conducted in South Africa, which compared SMS reminders to directly observed therapy short course (DOTS) reported similar rates of tuberculosis cure (62.35% vs. 66.4%) and treatment success (72.94% vs. 69.4%). A second study from South Africa, utilized SMS reminders when patients delayed in opening their pill bottles and reported increased tuberculosis cure (RR 2.32, 95% CI 1.60 to 3.36) and smear conversion (RR 1.62, 95% CI 1.09 to 2.42) rates compared to DOTS. In the third non-randomized study, conducted in Kenya, use of SMS reminders increased rates of clinic attendance on scheduled days compared to standard care (RR 1.56, 95% CI 1.06 to 2.29). Using the GRADE approach, we rate the quality of the evidence as low, mainly because of the high risk of bias and heterogeneity of effects across studies. This systematic review indicates that there is a paucity of high-quality data on the effectiveness of SMS interventions for improving patients' adherence to tuberculosis treatment. The low quality of the current evidence implies that further studies (in particular randomized trials) on the subject are needed. In the interim, if the intervention is implemented outside research settings an impact evaluation is warranted.